An update on the mechanisms and risk factors for anesthesia-related cardiac arrest in children: a narrative review - Braz, Leandro Gobbo [UNESP]; Braz, Jose Reinaldo Cerqueira [UNESP]; Tiradentes, Teofilo Augusto Araújo [UNESP]; Porto, Daniela de Sa Menezes [UNESP]; Beserra, Cristiano Martins [UNESP]; Vane, Luiz Antonio [UNESP]; Nascimento Junior, Paulo do [UNESP]; Modolo, Norma Sueli Pinheiro [UNESP]; Braz, Mariana Gobbo [UNESP] (Elsevier, 2024)
The relation between surgery and anesthesia safety in children and a country's Human Development Index (HDI) value has been described previously. The aim of this narrative review was to provide an update on the mechanisms and risk factors of Anesthesia-Related Cardiac Arrest (ARCA) in pediatric surgical patients in countries with different HDI values and over time (pre-2001 vs. 2001‒2024). Electronic databases were searched up to March 2024 for studies reporting ARCA events in children. HDI values range from 0 to 1 (very-high-HDI countries: ≥ 0.800, high-HDI countries: 0.700‒0.799, medium-HDI countries: 0.550‒0.699, and low-HDI countries: < 0.550). Independent of time, the proportion of children who suffered perioperative Cardiac Arrest (CA) attributed to anesthesia-related causes was higher in very-high-HDI countries (50%) than in countries with HDI values less than 0.8 (15‒36%), but ARCA rates were higher in countries with HDI values less than 0.8 than in very-high-HDI countries. Regardless of the HDI value, medication-related factors were the most common mechanism causing ARCA before 2001, while cardiovascular-related factors, mainly hypovolemia, and respiratory-related factors, including difficulty maintaining patent airways and adequate ventilation, were the major mechanisms in the present century. Independent of HDI value and time, a higher number of ARCA events occurred in children with heart disease and/or a history of cardiac surgery, those aged younger than one year, those with ASA physical status III‒V, and those who underwent emergency surgery. Many ARCA events were determined to be preventable. The implementation of specialized pediatric anesthesiology and training programs is crucial for anesthesia safety in children.
Keywords: Cardiac arrest; Children; Developed countries; Low-income countries